2021
DOI: 10.1002/jso.26554
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference in utilization of a perioperative treatment approach for gastric cancer between safety net hospitals and tertiary referral centers?

Abstract: Background and Objectives Perioperative therapy is a favored treatment strategy for gastric cancer. We sought to assess utilization of this approach at safety net hospitals (SNH) and tertiary referral centers (TRC). Materials and Methods Patients in the US Safety Net Collaborative (2012–2014) with resectable gastric cancer across five SNH and their sister TRC were included. Primary outcomes were receipt of neoadjuvant chemotherapy (NAC) and perioperative therapy. Results Of 284 patients, 36% and 64% received c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…However, a national study identified that utilization of NAT for GC patients with stage II–III disease remains under 50% in the United States 19 . In addition, studies have shown racial and socioeconomic disparities in access to MMT among GC patients that are associated with worse survival outcomes 20–22 . The association of higher incidence among minorities and complex interdisciplinary management might increase the risk of treatment and outcomes inequalities among GC patients across their cancer care continuum.…”
Section: Introductionmentioning
confidence: 99%
“…However, a national study identified that utilization of NAT for GC patients with stage II–III disease remains under 50% in the United States 19 . In addition, studies have shown racial and socioeconomic disparities in access to MMT among GC patients that are associated with worse survival outcomes 20–22 . The association of higher incidence among minorities and complex interdisciplinary management might increase the risk of treatment and outcomes inequalities among GC patients across their cancer care continuum.…”
Section: Introductionmentioning
confidence: 99%